Perancangan Buku Visual Desa Wisata Sasak Ende Sebagai Media Pelestarian Budaya Lombok - Dodi Irfansyah (Jurnal SASAK : Desain Visual dan Komunikasi, 2021)
Sasak Ende Tourism Village is a village that keeps a variety of cultural customs typical of the Sasak tribe (Lombok), where the local cultural customs are a state asset that deserves to be preserved, many people only know or don't know about the local cultural customs of the Sasak tribe ( Lombok), therefore we need a forum that can provide clearer information about the cultural customs of the Sasak tribe (Lombok). So that the researcher decided to make a media in the form of a visual book, in which the book contains images along with an explanation of the images, the use of simple words can make it easier for the audience to understand the contents of each attached page. The visual book "Sasak Ende Tourism Village" was designed with the Design Thinking method, which is a method that focuses on the target audience. Covering history, various buildings, customs and so on.